PERAN KEPOLISIAN DALAM PENANGGULANGAN TINDAK PIDANA PENADAHAN KENDARAAN BERMOTOR HASIL CURIAN (STUDI PADA POLRESTA BARELANG) - Mutia Anggraini; Lenny Lenny (JUSTITIA : Jurnal Ilmu Hukum dan Humaniora, 2021)
The criminal act of motorbike theft has a close relationship with the criminal act of detaining motorized vehicles by referring to data obtained from the Barelang Police which revealed 851 cases from 2018-2020, therefore the role of the police is important in overcoming criminal acts of detention based on the crime of theft. with the best possible. The purpose of writing this article is to answer the role of the police in overcoming the criminal act of detention by the Barelang Police and the obstacles faced by the police in overcoming the criminal act of detaining motorized vehicles stolen by the Barelang Police. The method used is juridical empirical, while the data analysis technique is qualitative. The results of research on the role of the police in overcoming the criminal act of detaining stolen motor vehicles by the Barelang Police, namely using an investigation strategy by seeking information from the public about the perpetrators of detention and interrogating the perpetrators of criminal theft in order to find the whereabouts of motorized vehicle holders The obstacles faced by the Barelang Police were the lack of public participation in providing information on the whereabouts of motorized vehicle holders and the lack of public awareness in protecting their vehicles.